Peran Pemahaman Metta dalam Perspektif Buddha untuk Meningkatkan Moral Remaja di SDS Cahaya Kasih Bengkayang - Kendi Kendi; Yadi Sutikno; Irawati Irawati (STAB Maitreyawira, 2022)
Fostering adolescent morale can apply the role of understanding Metta to adolescents, in that way it can teach teenagers to have metta traits, behave well, and have good manners. Metta is a sense of brotherhood, friendship, selfless help, having the will to do good, seeing other creatures as equal to oneself. Metta is also a desire to make others happy and get rid of hatred and evil desires that will hurt other people and other beings. Realizing the above, the writer tries to conduct a research that aims to describe the role of understanding metta to improve the morale of adolescents at SDS Cahaya Kasih Bengkayang with teaching based on love in a Buddhist perspective. This study uses descriptive qualitative research methods. The subjects in this study were the Principal, Educators of Buddhist Education Learning, Studentsand Parents of SDS Cahaya Kasih Bengkayang students. The object of this research is the role of understanding metta in the Buddhist perspective to improve the morale of adolescents at SDS Cahaya Kasih Bengkayang. The location of this research is at SDS Cahaya Kasih Bengkayang. Data collection techniques are the methods of observation, interviews, and documentation. And the results of the study show that the role of understanding metta in students at SDS Cahaya Kasih Bengkayang can be seen from the increased morale of students such as caring attitudes between others, honesty, politeness when speaking, respecting educators, helping each other, developing from understanding the role of metta.